2019
DOI: 10.5858/arpa.2018-0229-hp
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Causes of Death as Determined at Autopsy in a Single Institute, The Grant Medical College and Sir J. J. Hospital, Mumbai, India, Between 1884 and 1966: A Retrospective Analysis of 13 024 Autopsies in Adults

Abstract: Context.— Grant Medical College and Sir J. J. Hospital, Mumbai (India), have a long tradition of clinical autopsies, wherein autopsy records have existed since 1884. The old autopsy records from 1884 to 1966 were discovered during a refurbishing drive of the pathology department in 2007. Objective.— To know the relative causes of deaths in Sir J. J. Hospital Mumbai from 1884 through 1966. To determine the rate of antemortem and postmortem discrepancies in the prehistology and posthistology era. Design.— The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Despite inadequate knowledge, all family caregivers were aware of sudden death with the majority associating the cause with cardiac arrest. Several studies have reported this to be the case in sudden death worldwide (1)(2)(3)(4). This awareness reflects the high level of formal education of our respondents as the majority had tertiary education.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Despite inadequate knowledge, all family caregivers were aware of sudden death with the majority associating the cause with cardiac arrest. Several studies have reported this to be the case in sudden death worldwide (1)(2)(3)(4). This awareness reflects the high level of formal education of our respondents as the majority had tertiary education.…”
Section: Discussionsupporting
confidence: 55%
“…The cause of sudden death could vary, hence the need to conduct a postmortem examination in every case. Identifying the probable cause of death in apparently healthy individuals dying suddenly could enable the prevention of further deaths from this cause (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ratio of the body weight to the weights of the organs part IV: the kidneys, the spleen, the liver, the lungs, the pancreas, the pituitary, the suprarenals, the thyroid and the testes. In Reply.-We thank Pandya et al for their interest in our article 1 and their comments. To begin, we express our gratitude to Dr Purushottam Vishwanath Gharpure, MD, of Grant Medical College (GMC) (now Grant Government Medical College) and Sir J. J.…”
mentioning
confidence: 91%
“…He was awarded a Commander of the Order of the Indian Empire, at Queen Victoria's awards honors in 1897. 13 Finally, Lanjewar et al 1 12. Gharpure PV, Jhala HI.…”
mentioning
confidence: 99%